The Concept of Slow Living in the Qur’an: A Thematic Study of “Itsmun” and Learning Errors - Vachruddin, Vrisko Putra; Alawy, Muhammad Fahmi (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2025)
The position of teachers and students, who position themselves as human beings, cannot be separated from the concept of mistakes and sins committed intentionally or unintentionally. This refers to the Prophet's Hadith which states that every descendant of the Prophet Adam has certainly committed sin. Likewise, in the learning process, in order to understand the meaning of slow living (a peaceful life), a teacher must understand the mistakes in learning that occur between teachers and students, which can lead to sin between them. These mistakes need to be minimized by teachers and students by understanding the forms of error patterns in learning based on the thematic interpretation of the word itsmun in the verses of the Qur'an. This study uses a qualitative research type with a literature review research method and text analysis techniques. The word itsmun in the Qur'an is interpreted as a person who is sinful, an infidel, a liar, and each verse contains the meaning of opposing Allah and the Messenger and has a negative effect on oneself and others. The meaning of mistakes in learning made by teachers and students can be categorized as minor or major sins. In addition, in general, the categories of teacher and student mistakes are more directed towards human sins against the rights of society and the environment, as well as sins against oneself. The meaning of the phrase